The Importance of Organizational Agility to Improve Performance: An Evidence from the Hotel Industry in the Post-COVID-19 Era - Devie, Devie; Kwistianus, Hendri; Wellyani, Chantika Virginia Putri; Goenadi, Go Ruth Natasya Olivia (Binus Business Review, 2023)
The hospitality industry is one of the industries that experienced a hardest hit by the COVID-19 pandemic, such as a drastic drop in visitor levels and closed businesses. Despite the importance of organizational agility in the hospitality industry during post-pandemic recovery, there has been rare research on organizational agility in the hotel industry, especially in Indonesia. The research analyzed the effect of organizational agility on organizational performance through competitive advantage and organizational culture as mediating variables in hotels in Indonesia. The research sample was 76 hotels that consist of three-to-five-star hotels in Indonesia. The analysis was conducted using the Structural Equation Modeling (SEM) analysis method through smart Partial Least Square (PLS) software to test the research hypothesis. The results indicate that organizational agility plays an important role in increasing organizational performance. Organizational agility has a significant and positive impact on organizational performance in hospitality in Indonesia, with a competitive advantage and organizational culture as mediating variables. The research helps management to understand the importance of having organizational agility in a company to deal with uncertain conditions. The findings also help management not only focus on quality but also on how companies can meet customer needs, create competitiveness, take risks, innovate, and increase profitability to improve organizational performance.